KEWENANGAN PEMERINTAH DAERAH DALAM PELAKSANAAN PENGAWASAN DAN PENGENDALIAN KELAYAKAN FUNGSI BANGUNAN DI KOTA SURABAYA - Dwiluna Setiaprameswari; Rusdianto Sesung (Jurnal HUKUM BISNIS, 2023)
The development of the economy in the city of Surabaya has an impact on the rapid growth of building construction in the city of Surabaya. One of the Government's controls in ensuring the reliable implementation of building management is by issuing a Certificate of Proper Function to certify the feasibility of a building's function before it can be utilized. The Government's role in supervision and control must be carried out in order to ensure the fulfillment of building reliability aspects. This study aims to provide a description and analyze the authority of the Regional Government in carrying out supervision and controlling the feasibility of building functions in the city of Surabaya. This study tries to discuss the limits of the authority of the Regional Government on the implementation of supervision and control over the feasibility of building functions in the city of Surabaya and the imposition of sanctions on building owners who violate the feasibility of building functions based on the results of supervision and control by the Surabaya city government. The conclusion of this study is that the authority of the local government to supervise and control the feasibility of building functions in the city of Surabaya is limited by the period, area and substance of authority, while the forms of sanctions against building owners who violate the feasibility of building functions are based on the results of supervision and control by the Surabaya city government in the form of administrative sanctions, fines and criminal penalties. To apply fines and criminal sanctions, the Surabaya city government needs to develop a legal basis regarding the intent, purpose and scope of imposing sanctions and the procedures for implementing them.Keywords: feasibility of building functions, supervision and control